Set3 Is Required for Asexual Development, Aflatoxin Biosynthesis, and Fungal Virulence in Aspergillus flavus - Lan, Huahui; Wu, Lianghuan; Fan, Kun; Sun, Ruilin; Yang, Guang; Zhang, Feng; Yang, Kunlong; Lin, Xiaolu; Chen, Yanhong; Tian, Jun; Wang, Shihua (Frontiers in Microbiology, 2019)
Aspergillus flavus is an opportunistic pathogenic fungus for both plant and animal that produces carcinogenic toxins termed aflatoxins (AFs). To identify possible genetic targets to reduce AF contamination, in this study, we have characterized a novel A. flavus Set3, and it shares sequence homology with the yeast protein Set3. The set3 deletion mutants present no difference in growth rate but alterations in asexual development and secondary metabolite production when compared to the A. flavus wild type. Specifically, deletion of set3 gene decreases conidiophore formation and conidial production through downregulating expression of brlA and abaA genes. In addition, normal levels of set3 are required for sclerotial development and expression of sclerotia-related genes nsdC and sclR. Further analyses demonstrated that Set3 negatively regulates AF production as well as the concomitant expression of genes in the AF gene cluster. Importantly, our results also display that A. flavus Set3 is involved in crop kernel colonization. Taking together, these results reveal that a novel Set3 plays crucial roles in morphological development, secondary metabolism, and fungal virulence in A. flavus.